2010
DOI: 10.1039/c0cc00098a
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[1,2-b:4,5-b′]dithiophene-dioxopyrrolothiophen copolymers for high performance solar cells

Abstract: New donor/acceptor polymers PBDTDPT1 and PBDTDPT2 with alternating benzodithiophene and N-alkylated dioxopyrrolo-thiophene were synthesized. The new polymers had deep HOMO levels of -5.42 and -5.44 eV for PBDTDPT1 and PBDTDPT2, respectively. A PBDTDPT2 based BHJ solar cell device achieved a PCE of 4.79% and V(oc) of 0.91 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(114 citation statements)
references
References 27 publications
4
110
0
Order By: Relevance
“…In the search for novel polymers suitable for PSCs, Leclerc [146], Jen [147], Xie [148], and Frechet [149] independently synthesized PBDTTPD, which included the benzodithiophene (BDT) unit as donor moiety and TPD as acceptor moiety. The preliminary PCE of the PBDTTPD/PC 71 BM-based PSC device was as high as 5.5 % without additive optimization [146].…”
Section: Thienopyrroledione (Tpd)-based Polymersmentioning
confidence: 99%
“…In the search for novel polymers suitable for PSCs, Leclerc [146], Jen [147], Xie [148], and Frechet [149] independently synthesized PBDTTPD, which included the benzodithiophene (BDT) unit as donor moiety and TPD as acceptor moiety. The preliminary PCE of the PBDTTPD/PC 71 BM-based PSC device was as high as 5.5 % without additive optimization [146].…”
Section: Thienopyrroledione (Tpd)-based Polymersmentioning
confidence: 99%
“…As expected, a slightly deep HOMO level of −5.61 eV was got. And when fabricated solar cell with PC 61 BM as the acceptor, the device exhibited a moderate PCE of 6.17% with a V oc of 1.00 V, a J sc of 9.79 mA/cm 2 and a FF of 63% (Table 2) [81].…”
Section: Thieno[34-c]pyrrole-46-dione Based Polymersmentioning
confidence: 99%
“…The detailed synthetic procedures of monomer 3 are described in Scheme 1 and fully characterized by conventional 1 H NMR, 13 …”
Section: Synthesis Of the Copolymersmentioning
confidence: 99%
“…[6] Thieno [3,4-c]pyrrole-4,6-dione (TPD), [7,8] an electron-deficient building block, was first utilized for the synthesis of D-A copolymers in 1998. [9] Then several research groups independently reported a new kind of mid-bandgap copolymers based on the TPD and weak electron-donating benzodithiophene (BDT) moieties, [10][11][12][13][14][15] suggesting the good potential of TPD-based copolymers in PSC applications and a high power conversion efficiency (PCE) of 8.5% was obtained by further side-chain tuning. [16] Recently, Hwang and co-workers reported a TPD-based D-π-A copolymer with a medium optical bandgap of 1.75 eV that delivered the so far highest PCE of 9.21% among TPD-polymers.…”
Section: Introductionmentioning
confidence: 99%